Effect of the Toll-Like Receptor 4 Antagonist Eritoran on Retinochoroidal Inflammatory Damage in a Rat Model of Endotoxin-Induced Inflammation - Feyzahan Ekici; Emine Esra Karaca; Şafak Korkmaz; Osman Yüksel; Özlem Gülbahar; Murat Alper; Sevim Ercan; Meral Or (Mediators of Inflammation)
Purpose. We investigated the effect of eritoran, a Toll-like receptor 4 antagonist, on retinochoroidal inflammatory damage in an endotoxin-induced inflammatory rat model. Methods. Endotoxin-induced inflammatory model was obtained by intraperitoneal injection of 1.5 mg/kg lipopolysaccharide (LPS). Group 1 had control rats; in groups 2-3 LPS and 0.5 mg/kg sterile saline were injected; and in groups 4-5 LPS and 0.5 mg/kg eritoran were injected. Blood samples were taken and eyes were enucleated after 12 hours (h) (groups 2 and 4) or 24 hours (Groups 3 and 5). Tumor necrosis factor-α (TNF-α) and malondialdehyde (MDA) levels in the serum and retinochoroidal tissue and nuclear factor kappa-B (NFκB) levels in retinochoroidal tissue were determined. Histopathological examination was performed and retinochoroidal changes were scored. Results. Eritoran treatment resulted in lower levels of TNF-α, MDA, and NFκB after 12 h which became significant after 24 h. Serum TNF-α and retinochoroidal tissue NFκB levels were similar to control animals at the 24th h of the study. Eritoran significantly reversed histopathological damage after 24 h. Conclusions. Eritoran treatment resulted in less inflammatory damage in terms of serum and retinochoroidal tissue parameters.